Math, asked by harshikaprabhakar, 1 year ago


4 \sqrt{3}  - 3 \sqrt{12}  + 2 \sqrt{75}

Answers

Answered by anshgupta203pepu50
0
√12=2√3 and √75=5√3
so now all terms are like terms.
4√3-6√3+10√3= 8√3
Answered by Ashishkumar098
1
ᴇʟʟᴏ!!

ʜᴇʀᴇ's ʏᴏᴜʀ ᴀɴsᴡᴇʀ

______________________

4 √3 - 3 √12 + 2 √75

= 4 √3 - 3 √( 3 × 2 × 2 ) + 2 √ ( 3 × 5 × 5 )

= 4 √3 - 3 × 2 √3 + 2 × 5 √3

= 4 √3 - 6 √3 + 10 √3

= 8 √3

______________________

ʜᴏᴘᴇ ɪᴛ ʜᴇʟᴘs ʏᴏᴜ ᴅᴇᴀʀ!

★ ᴅᴇᴠɪʟ ᴋɪɴɢ

harshikaprabhakar: Thanks
Ashishkumar098: no problem
Ashishkumar098: hope it helps you
Ashishkumar098: :)
harshikaprabhakar: ya it's helpful
Ashishkumar098: :)
harshikaprabhakar: ya
Similar questions